Education by experience : Coding projects as a purpose within an educational experience in mathematics - da Silva Barbosa, Luciana Leal (2023)
This work aims to present and discuss John Dewey's philosophy of experience, emphasizing his conceptions about experience, educational experience, and purpose. In addition, to present and discuss how the programming projects developed by children in Scratch can be understood as a purpose in the context of his philosophy, which led us to relate the concept of purpose constructed by Dewey to the idea of a personal project developed by Papert, within constructionism. Such a relationship becomes important to expand the investigations that deal with problems related to the teaching of programming in basic education. To exemplify the possible relationships, we present a programming project developed by a K-5 school student, recognizing in it the theoretical assumptions of Dewey's theory discussed in the text, relating them to Papert’s ideas.